Kahoot-based gamified learning media integrated with problem-based learning to enhance elementary school students’ critical thinking and learning motivation - Nopianti, Resti; Jaenudin, Dadang; Hendriana, Heris (Indonesian Journal of Science and Mathematics Education, 2026)
This study aims to develop media using Kahoot with Problem-Based Learning (PBL) to enhance elementary school students' critical thinking and learning motivation. This study uses the Research and Development (R and D) approach using the ADDIE model. This study was conducted at Cibadak 01 Public Elementary School, involving 34 sixth-grade students. Data collection techniques included tests, questionnaires, and validation sheets. The results indicate that the developed media is highly feasible based on experts’ validation and effectively improves students' critical thinking skills, as reflected in the significant increase between pretest and posttest results. The N-Gain score of 0.6763 indicates a moderate level of effectiveness. In addition, students showed very positive responses, indicating increased learning motivation during the learning process, as reached 91.9% in the very positive category. This study contributes to the integration of gamification and PBL by providing effective and innovative learning media in elementary education that support domain-specific critical thinking development. Furthermore, theoretically, this study strengthens the role of gamification-based learning in enhancing higher-order thinking skills and student engagement. Practically, it offers an applicable digital learning solution for teachers to design interactive and motivating mathematics classroom environments that systematically foster critical thinking across its core domains.